Framework mekanisme tata kelola dan sumber daya manusia untuk efektifitas aliran informasi - Mardiana, Sylvia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study develops a framework of governance mechanisms and human resource capabilities for the effective flow of information within the organization. This research is an exploratory research based on secondary data using a literature study methodology. The results of the synthesis show that the governance mechanism determines the success of information flow. The results also indicate the need for human resource capabilities to support governance and information sharing mechanisms. There are two types of governance mechanisms: formal and informal governance. Formal governance includes contracts, business processes, performance appraisal and information systems, and cross-functional teams. Meanwhile, informal governance includes trust, commitment, power and social interaction. Human resources with systems thinking, mastery of technology, and interpersonal skills are very valuable for sharing information. This study helps to understand the factors that affect the effectiveness of information flow.